2016
DOI: 10.1890/15-0153.1
|View full text |Cite
|
Sign up to set email alerts
|

Beyond arctic and alpine: the influence of winter climate on temperate ecosystems

Abstract: Winter climate is expected to change under future climate scenarios, yet the majority of winter ecology research is focused in cold-climate ecosystems. In many temperate systems, it is unclear how winter climate relates to biotic responses during the growing season. The objective of this study was to examine how winter weather relates to plant and animal communities in a variety of terrestrial ecosystems ranging from warm deserts to alpine tundra. Specifically, we examined the association between winter weathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…Determining how assemblages respond to interannual climate variability can provide insights into mechanisms behind long-term changes and can indicate how rapidly communities might respond to future climate change (Ladwig et al, 2016;Ozkundakci et al, 2016). There is still a poor understanding for how climate variability impacts entire assemblages, which consist of many species with variable dispersal abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Determining how assemblages respond to interannual climate variability can provide insights into mechanisms behind long-term changes and can indicate how rapidly communities might respond to future climate change (Ladwig et al, 2016;Ozkundakci et al, 2016). There is still a poor understanding for how climate variability impacts entire assemblages, which consist of many species with variable dispersal abilities.…”
Section: Introductionmentioning
confidence: 99%
“… Hourly temperature with 50% probability (continual 12 h/d) of freezing (below 0°C) is defined as beginning and end of winter in this study (modified from Ladwig et al. ). This definition is not conservative because solar radiation is very strong in this alpine forest and increases in temperature were recorded by data logger. …”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies found that snow cover and soil freezing/thawing in winter significantly influence litter decomposition (Wu et al 2010), so we divided each year into a winter season and a growing season. The winter season was defined as the period of successive days in which hourly temperatures were freezing (below 0°C) for at least 12 h of the day (Table 2; Ladwig et al 2016). Samplings were scheduled for the end of the winter season and growing season each year, at which time two litterbags were randomly collected per subplot (a total of 12 subplots for each litter type), carefully placed into separate plastic bags and returned to the laboratory.…”
Section: Sampling and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Winter climate is influential in many ecosystems (Ladwig et al., ) and experimental manipulations help examine the response of ecological systems to changing winter conditions (Kreyling, ). Snow manipulations test for the ecological consequences of altered winter precipitation (Kreyling, Haei, & Laudon, ; Loik, Griffith, & Alpert, ), and warming manipulations track ecosystem changes following gradual increases in temperature (Collins et al., ; Wu, Dijkstra, Koch, Penuelas, & Hungate, ), yet our understanding of the response of plant communities to winter climate extremes is often limited to opportunistic studies following extreme climate events, as large‐scale cooling experiments are generally not practical.…”
Section: Introductionmentioning
confidence: 99%